(untitled) (Asian Journal of Medical and Biological Research, 2020)
Moringa is a valuable plant whose leaves are enriched with antioxidants, amino acids, vitamins and mineral nutrients and can be used as a bio-stimulant. A field work was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University (BAU), Mymensingh, during rabi season from November 2017 to February 2018 in order to investigate the effect of moringa leaf extract (MLE) on growth, yield and nutrient status of cabbage. The experiment was laid out in a randomized complete block design with four treatments and three replications. The treatments were T1 (control), T2 (MLE) sprayed at 2 weeks after transplanting only], T3 (MLE sprayed at 2 weeks and 4 weeks after transplanting), T4(MLE sprayed at 2 weeks after transplanting and after every two weeks thereafter). The rate of MLE application was 25 mL plant-1. All the treatments received recommended dose of N, P, K, S, Zn and B fertilizers. The application of MLE significantly improved the growth parameters, yield and yield contributing characters as well as nutrient content and uptake of cabbage. Among the parameters plant height (33.40 cm), leaf number (19.33 cm), length of the largest leaf (29.00 cm), head thickness (9.67 cm), head diameter (20.33 cm), gross yield (72.83 t ha-1) and marketable yield (48.87 t ha-1), were maximum in T4 where MLE was sprayed at 2 weeks after transplanting and after every two weeks thereafter. The lowest values of all these parameters were found in T1 where no MLE was sprayed. Foliar application of MLE also improved the concentration and uptake of macronutrients (N, P, K and S) in head of cabbage. Thus, application of MLE as a bio-stimulant has the potentiality to enhance growth, yield and nutritional quality of cabbage. Asian J. Med. Biol. Res. June 2020, 6(2): 196-203